HUBUNGAN ANTARA BUDAYA ORGANISASI DAN KEPUASAN KERJA DENGAN KOMITMEN TERHADAP ORGANISASI - Herman Herman (Universitas Pakuan, 2018)
AbstractThe purpose of this study was to determine whether there is a relationship between organizational culture and job satisfaction with a commitment to the organization (Study Tous Les Jours Employees In Bakery). The population in this study was overall Tous Les Jours Bakery employees as much as 364 people, while that will serve as the study sample were employees of the Kitchen staff totaling 200 people. Slovin formula samples using as many as 133 people. The research instrument was a questionnaire. The collected data was then processed using correlation analysis techniques with the help of software SPSS (Statistical Package for Social Science). The results showed that: First of organizational culture on organizational commitment has a significant relationship and has a contribution of 11.3%. Both job satisfaction and commitment to the organization has a very significant relationship and has a contribution of 21.7%. The third organizational culture and job satisfaction together have a very significant relationship and have contributed 25.7%, the remaining 74.3% is determined by other variables not examined.Keywords: Organizational Culture, Job Satisfaction and Commitment to the Organization.